(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
The aim of this paper is to establish the impact of revenue and expenditure management on sports events organized by non-profit sports organizations. The subject of the case study is futsal, a team sport known also as five-a-side football which is popular at the recreational level in the Republic of Croatia, has a long history and relatively low organizational costs. The geographical area of the analysis includes five eastern counties of the Republic of Croatia, while the analyzed format of the competition is the one where teams compete for several months, i.e., an entire season. These are amateur competitions where the goal set by the organizer is the development and popularization of the sport, rather than profit. The primary research included in-depth interviews with responsible persons within county football centers and subsequently the organizers of the competitions being held. After the information was obtained, the revenue and expenditure structure, as well as costs of an individual team per played match, were analyzed. Based on this information, through secondary research, publicly available data on individual costs when organizing a sports competition were obtained, and a projection of a sustainable budget was made by balancing its revenue and expenditure aspects. The analysis of the expenditure structure established fixed and variable costs as well as their effect on project sustainability. In accordance with all the results obtained, the main factors of financial difficulties for the sports organizations organizing such competitions were detected, while the conclusion suggests several specific measures possible for overcoming such difficulties.